Dampak Intelectual Capital Terhadap Sustainability Report Dan Kinerja Perusahaan Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2017-2021 - Nuraeni; Silviyatul Laila (LPPM POLITEKNIK LP3I BANDUNG, 2024)
The purpose of this research is to quantify the effect that intellectual capital has on the transparency of sustainability reports and the financial health of Indonesian banking firms traded on the IDX between 2017 and 2021. Purposive sampling was used to determine the number of firms to be tested (up to 46), and 18 financial institutions were sampled. Partial Least Square (WarpPLS 7.0) was used for all measurements and data analysis. The research found that (1) intellectual capital affects financial institution performance, (2) I.C. also affects the disclosure of sustainability reports, and (3) S.R.s had no impact on financial institution performance.